Pengembangan Sumberdaya Aparatur Pemerintahan Daerah di Kabupaten Tulungagung - Ismail, H. M. (Universitas Brawijaya, Indonesia, 2008)
Human resource development of apparatus is one of idea to develop ability as a creative process 10 create a good governance. Qualification, intellegentia, and professionalism of apparatus human resource becomes the dominant factor to build good governance. The apparatus should be able to adapt with system change independently and also build the capacity institutionally. The research formulates the questions: (1) What is the mechanism of human resource development of apparatus that is designed by Tulungagung government?; (2) How to implement its policy in accordance with human resource development of its apparatus?; (3) What some supporting and disturbing factors in building Tulungagung government apparatus human resource? The research recommends the importance of formulation local regulations in relation with the local human resource development by adjusting its needs and demands of local public service.